Influence of Corporate Social Responsibility Disclosure on financial performance of manufacturing companies listed on Indonesia Stock Exchange - Ayu Chairina Laksmi; Adella Puspita Hasri (Jurnal Akuntansi dan Auditing Indonesia, 2022)
This study aimed to investigate the influence of Corporate Social Responsibility Disclosure (CSRD) on companies’ financial performance which was proxied by Return on Assets (ROA), Return on Equity (ROE), and Earning per Share (EPS). The analysis was conducted on the annual reports of 31 manufacturing companies that were listed on the IDX from 2016 to 2019. A purposive sampling method was employed to select samples from the population. The data analysis was performed by using SPSS Statistics for Windows, Version 21. The results indicated that CSRD had significant positive influences on ROA and ROE, but CSRD did not have an influence on EPS. The findings of this study can be a consideration for companies’ decision making related to their CSRD which is important for their public image and profit-making activities. Investors can also benefit from the study by using CSRD as a reference in making investment decisions. Lastly, the government can use this study to evaluate the implementation of compulsory CSRD in companies in Indonesia.